Targeting Pericytes for Vascular Normalization as an Emerging Strategy in Remodeling Tumor Microenvironment - LAO Shen, HE Jianxing, LIANG Wenhua (Zhongguo quanke yixue, 2022)
Recent studies demonstrate that, the close interactions between pericytes (PCs) and various cells (such as cancer cells, stromal cells and immune cells) in tumor microenvironment (TME) can build an immunosuppressive TME to favor cancer growth and progression by modulating tumor angiogenesis and dysfunction via abnormal paracrine signaling pathways. In this review, we focused on recent advances in non-small-cell-lung-cancer to understand the regulatory role of PCs in TME and discussed the potential value of targeting PCs for inhibiting tumor angiogenesis and normalizing tumor vasculature to remodel TME, indicating that we can break through the dilemma of combined anti vascular therapy for solid tumors at this stage by targeting the normalization of tumor blood vessels of PCs. This may be a new strategy that could be used combinedly to improve chemotherapy, small molecule inhibitor targeted therapy or immune checkpoint inhibitor therapy.